Windows Server 2003 - Pocket Administrator - Ruest Nelson; Rusest Danielle (American : McGraw -Hill, 2003)
Contents of text
This handy resource offers busy network administrators clear and concise information for daily on-the-job tasks--all in a portable format. Key management tasks are presented in logically organized sections. You’ll get details on file, print, application, mail, terminal, streaming media, and remote servers--and much more.
Keywords: Tin học--Hệ điều hành; Windows Server 2003